Heavy metal concentrations in water, sediments, Cladophora and two fish species from Al-Masab Alamm River, Al- Nassiriya, Iraq - Sanaa Talib Jawad; Ahmed F. Shihab; Qasim Muhammad Al-Taher (Caspian Journal of Environmental Sciences, 2022)
Heavy metal pollution is a serious threat for human health relating to their toxicity and bioaccumulation in the food chain which made this problem as global public health issue. The current study aimed to determine the heavy metal concentrations and their toxicity in water, sediment, Cladophora and the gill, liver and muscle of Liza abu and Barbus barbus in Al-Masab Alamm River, Al Nassiriya, Iraq. The samples were included thirty fishes and there were three selected sample stations covered the area on the river. The heavy metal   levels were determined using an atomic absorption spectrophotometer (AAS). The results showed that the heavy metal concentrations in water, sediment, algae and the sampled fishes exceeded the acceptable levels for World Health Organization and Food and Agriculture Organization of the United Nations. Heavy metal levels were estimated in different tissues of fish. The results revealed that most of the heavy metal concentrations were high in gills, liver and muscles respectively. Lead and copper accumulated higher in liver than in the other tissues.